A Reformation of Remembrance? Devotional Practices of Female Testators in Lincolnshire 1509-1558. (3rd July 2019) - Wilson, Marianne
ABSTRACT: This article examines the pious and commemorative practices of female testators in the Lincolnshire wills proved at the Prerogative Court of Canterbury between 1509 and 1558, held at The National Archives. Lincolnshire was one of the largest counties and formed part of the largest diocese in the country, so it provides a geographically extensive case study of female testamentary practice, important because the rate of female testators is low. Wills provided an opportunity for women to shape their pious identities and choose how they wished to be remembered after their deaths. Changing government policies impacted upon female attitudes towards remembrance and material culture and the ideals of the new Protestant religion also affected the nature of post-mortem charitable provision. The article explores how far these wills can be used to trace changes in religious attitudes across the period of the early Reformation in Lincolnshire.